Designing an Intelligent Coach for a Collaborative Concept-Mapping Learning Environment - Fang-Fang, Chua; Chien-Sing, Lee (SPRINGER-VERLAG BERLIN, 2008)
Education should emphasize more on the process of creating conducive environments rather than merely on the product of learning. Merlin is a collaborative and cognitive tool that enables the students to express and visualize their ideas to their peers. By reviewing various types of coaching techniques being used by different tutoring systems, we aim to identify suitable mapping between a tutoring aim and its corresponding coaching technique as well as any possible drawbacks. Results of the comparative analyses will be used to determine how Merlin agents can improve mapping between the adaptation and pedagogical modules in ITSs, leading to more effective adaptation of tutoring strategies.